KONTRUKSI BATTRY TEST KETERAMPILAN BOLA BASKET UNTUK SISWA SEKOLAH DASAR KOTA BENGKULU - Feby Elra Perdima; Algifari Syarif (Journal Physical Education, Health and Recreation, 2018)
The teacher gave material about basketball but it was constrained in the final practice test regarding the form of basketball skills test. This was seen during observations at schools in Bengkulu city. In generally, method of assessment in basketball material was in the form of a battery tests, but the tests used for the assessment were less effective. The aim of this research is to create instrument test of passing, shooting and dribble in basketball for Elementary School Students of Bengkulu City aged 10-13 years with a sample of 50 male students. The instrument of this research was a skill test of Battery Test that was modified by the researcher so that it got a valid and reliable instrument for elementary school students with validity of dribbling is 0.65, passing is 0.78 and shooting is 0.73. Furthermore, the reliable of dribbling is 0.85, passing is 0.85 and shooting is 0.78.